RETRACTED: Regulatory roles of epigenetic modulators, modifiers and mediators in lung cancer. (February 2017) - Shi, Lin; Zheng, Minghuan; Hou, Jiayuan; Zhu, Bijun; Wang, Xiangdong
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/our-business/policies/article-withdrawal ). This article has been retracted at the request of the Editor-in-Chief as well as the authors. The article includes substantial parts copied without attribution of the article: Nat Rev Genet. 2016 May;17(5):284-99.doi:10.1038/nrg.2016.13 . Epub 2016 Mar 14. Epigenetic modulators, modifiers and mediators in cancer aetiology and progression. Feinberg AP, Koldobskiy MA, Göndör A.